How disease threat affects the purchase intention of ultra-processed foods among high-pressure workers - He, Linli; Yang, Dajun; Huang, Yifan (Frontiers in Nutrition, 2025)
IntroductionThe continuous outbreak of global epidemics has highlighted the impact of disease threats on consumer behavior. While prior research has examined the influence of disease threats on consumer decisions, few studies have explored their specific effect on the purchase intention of ultra-processed foods among high-pressure workers. This study examines how disease threats affect the purchase intention of ultra-processed foods among this group.MethodsWe conducted three experiments with 828 participants, employing Process Model 4 and Model 1 to analyze the relationship between disease threats, health perception, fear, and the intention to purchase ultra-processed foods.ResultOur findings indicate that disease threats significantly reduce the purchase intention of ultra-processed foods among high-pressure workers, with health perception serving as a mediator of this relationship. Additionally, fear interacts with disease threats to further shape purchase behavior.ConclusionThis research offers novel insights into the consumption patterns of high-pressure workers under disease threats, providing theoretical guidance for public health policies and marketing strategies.